The Effect Of Banana Mas Flour Substitution On The Quality Of Semprit Cookies - Thesya Firdayanti R.P; Wirnelis Syarif (Universitas Negeri Padang, 2021)
Cookies are one type of pastry product that people like. Cookies have many variations, one of which is a syringe cookie. Spray cookies are spray cookies that have a sweet taste, made from the basic ingredients of wheat flour, fat with a syringe technique. Wheat flour as the main ingredient for making cookies can be replaced by using banana flour. This study aims to analyze the effect of banana flour substitution on the quality of the syringe cookies with the percentages of 0%, 25%, 50%, and 75% on the organoleptic test of the shape, color, aroma, texture, and taste of the syringe cookies. This type of research is a pure experiment using a completely randomized design (CRD) method with four treatments and three repetitions. The data collection technique was carried out by giving questionnaires to 5 expert panelists who were lecturers of Family Welfare Science with the concentration of UNP Cuisine with primary data types. The data were analyzed using ANAVA, if Fcount Ftable then continued with Duncan's test. The results of this study indicate that there is a significant effect on the quality of the syringe cookies except for the shape, color, and sweet taste. The results of the quality of the best banana flour substitution syringe cookies were in the second treatment (X1) with a percentage of 25%.